Percepción De Estrés Y Prácticas Parentales En Estudiantes De Psicología De Nuevo Ingreso - José Esael Pineda Sánchez; Rosa Mariela González Hernández; Angélica Romero Palencia; Rebeca Guzmán-Saldaña (European Scientific Journal, ESJ, 2017)
The entrance to the university life causes changes and demands that generate high stress and difficulties for the adaptation. There is evidence that parental overinvolvement, specifically psychological control (induction of guilt or disqualification), causes problems in the psychosocial adjustment of children and adolescents. Few studies address the impact of parental practices on the adaptive processes of young adults. The aim of the present study was to describe, compare by sexes, and associate the perception of stress and prevailing parental practices among college admission students of psychology career. A non-experimental transectional, comparativecorrelational study was performed 127 students (70.08% female, 29.92% male) with an average age of 19 from a public university in Hidalgo, Mexico participated. The Scale of Parental Practices for Adolescents (Andrade & Betancourt, 2008) and the Stress Perception Scale (González & Landero, 2007) were applied. No differences were found between men and women in the perception of stress, but in parental practices of maternal communication, maternal knowledge about son activities and induction of guilt, devaluation and excessive maternal criticism were found differences. Likewise, correlations between stress and the dimensions of maternal-filial respect, maternal imposition, induction of guilt, devaluation and excessive criticism, paternal-filial respect and paternal imposition on women were found; and between paternal and filial stress and respect in males. It is suggested that the role of parents in child rearing has a greater impact on the adaptive behavior of women in university life.